MiR-302a Limits Vascular Inflammation by Suppressing Nuclear Factor-κ B Pathway in Endothelial Cells - Yuan, Jia-Ni; Hong, Yu; Ma, Zhuo-Lin; Pang, Rui-Ping; Lei, Qing-Qing; Lv, Xiao-Fei; Zhou, Jia-Guo; Huang, Hui; Zhang, Ting-Ting (Frontiers in Cell and Developmental Biology, 2021)
The inflammatory response of endothelial cells accelerates various vascular diseases. MicroRNAs (miRNAs) participate in diverse cellular processes during inflammation. In the present study, we found that miR-302a is an effective suppressor of vascular inflammation in endothelial cells. It was revealed that miR-302a exhibited a lower level in a lipopolysaccharide (LPS)-induced mouse model and in patients with vascular inflammatory disease. Genetic haploinsufficiency of miR-302 aggravated the LPS-induced vascular inflammatory response in mice, and overexpression of miR-302a attenuated vascular inflammation in mice. Furthermore, overexpression of miR-302a inhibited the synthesis and secretion of adhesion factors in endothelial cells, and suppressed the adhesion of monocytes to endothelium. In the study of molecular mechanism, we found that miR-302a relieved vascular inflammation mainly by regulating the nuclear factor kappa-B (NF-κB) pathway in endothelial cells. The results showed that interleukin-1 receptor-associated kinase4 (IRAK4) and zinc finger protein 91 (ZFP91) were the binding targets of miR-302a. MiR-302a prevented the nuclear translocation of NF-κB by inhibiting phosphorylation of IκB kinase complex β (IKKβ) and inhibitors of κBα (IκBα) via targeting IRAK4. In addition, miR-302a downregulated the expression of NF-κB by directly binding with ZFP91. These findings indicate that miR-302a negatively regulates inflammatory responses in the endothelium via the NF-κB pathway and it may be a novel target for relieving vascular inflammation.